2002
DOI: 10.2165/00126839-200203060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Toxicity Study of Oral Administration of D-003 in Sprague Dawley Rats

Abstract: It was concluded that the highest studied dose of D-003 (1,000 mg/kg/day) represented a non-toxic dose level in the present chronic toxicity study in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The reason for the increased body weight of the satellite 1000 mg/kg bw group is still uncertain. The weight gain of the satellite 1000 mg/kg bw group in this current study was still in a normal range [20]. A possible explanation is as follows: tamarind pulp water extract has an effect of inhibition of weight gain [16].…”
Section: Discussionmentioning
confidence: 89%
“…The reason for the increased body weight of the satellite 1000 mg/kg bw group is still uncertain. The weight gain of the satellite 1000 mg/kg bw group in this current study was still in a normal range [20]. A possible explanation is as follows: tamarind pulp water extract has an effect of inhibition of weight gain [16].…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the negative contribution of D-003 for reinforcing the mechanisms of liver toxicity induced with galactosamine is consistent with its lack of hepatotoxicity found in previous toxicological studies. 43,44 In such regard, the fact that D-003 can protect from liver damage induced by agents increasing LP processes is interesting, since it is uncommon for cholesterol-lowering drugs, associated with increases of transaminases and others features indicative of liver toxic- ity. Thus, a cholesterol-lowering drug devoid of liver toxicity is promising for treating patients with hypercholesterolemia at high coronary risk, but difficult to manage with drug therapy due to disturbances of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of oral toxicity of D-003 in rodents (acute, subchronic, and chronic) have shown that it did not induce drug-related toxicity. [18][19][20] Similarly, the in vitro and in vivo assessment of cytotoxic and/or genotoxic potential effects of D-003 showed that D-003 was devoid of cytotoxic or genotoxic potential, 21,22 and the lack of reproductive toxicity has been also documented for D-003. 23 Nevertheless, information about putative drug-to-drug interactions between D-003 and other drugs commonly consumed is scarce, being limited to isolated experiences of pharmacodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%